Hepatic and cardiac iron overload quantified by magnetic resonance imaging in patients on hemodialysis: A systematic review and meta‐analysis. Issue 1 (17th November 2022) - Nashwan, Abdulqadir J.; Yassin, Mohamed A.; Abd‐Alrazaq, Alaa; Shuweihdi, Farag; Othman, Muftah; Abdul Rahim, Hanan F.; Shraim, Mujahed
Abstract: Introduction: Few studies have reported hepatic and cardiac iron overload in patients with end‐stage renal disease (ESRD), and the current evidence regarding the prevalence is still scarce. Aim: This review aims to estimate the prevalence of hepatic and/or cardiac iron overload quantified by magnetic resonance imaging (MRI) in patients with ESRD who receive hemodialysis (HD), peritoneal dialysis (PD), or have undergone a kidney transplant. Methods: A systematic review with meta‐analysis was conducted and reported in line with PRISMA (Preferred Reporting Items for Systematic Review and Meta‐Analysis) guidelines. MEDLINE and Embase bibliographic databases were searched using a comprehensive list of controlled vocabulary and keywords to identify relevant studies. All studies reporting the prevalence of hepatic and/or cardiac iron overload quantified by MRI in ESRD patients were considered. The Newcastle‐Ottawa scale was used to assess the methodological quality of included studies. To investigate the heterogeneity between studies, random‐effect meta‐analyses for proportions were used. Results: The review comprised seven studies that included 339 patients. Using meta‐analysis, the pooled prevalence of severe and mild to moderate hepatic iron overload quantified by MRI was 0.23 [95% CI: 0.08–0.43] and 0.52 [95% CI: 0.47–0.57], respectively. Only three studies included cardiac iron quantification, and none reported iron overload. Conclusions: This review has revealed a high prevalence of severe hepatic iron overload in patients with ESRD treated by HD. Further studies with a larger sample size are needed to determine the impact of iron overload on vital organs in patients with ESRD and guide future research in this understudied field. Proper use of iron chelation and continuous monitoring will help in the early detection of unsolicited complications; however, the low renal clearance of most iron chelators limits the options for treating iron excess in patients with ESRD.